Borrowing Agreement with the Government of Canada. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper presents for the approval of the Executive Board a draft borrowing agreement between the Government of Canada and the Fund. The Government of Canada announced its willingness to lend up to USD 10 billion to the Fund to support the Fund's ability to provide timely and effective balance of payments assistance to its members in the context of the summit of the Leaders of the Group of Twenty (G-20) in early April. Staff and the Canadian authorities have now reached agreement on a draft borrowing agreement, the text of which is set forth in the Attachment (the 'Agreement'). The Agreement would make an important contribution to the multilateral effort to ensure the adequacy of the Fund's financial resources, adding to the resources already available to the Fund from the borrowing agreements with Japan and Norges Bank that were approved by the Board recently. It is also expected that borrowing agreements with other members will be proposed for Board approval soon.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Agreement; Borrowing Agreement; Fund; Japan Agreement; PP; Canada